(untitled) (International Journal of Food and Nutritional Sciences, 2022)
We know that liquid crystal is of immense importance now-a-days. In the liquid crystal mixture, we have studied thermo optical properties as a function of temperature. The main feature of optical phenomena in liquid crystal causes due to thermo optical and phase transition procedure. Thermal effect is similar as in other materials. While the phase transition is the characteristic property which we find in liquid crystalline phases. The nonlinearity occurs due the reorientation effect in case of nematic phase that results to many other effects also which are not observed in any other type of nonlinearity. The nonlinearity depends on polarization of light within a wide range. It is independent of wavelength of light. It has slow response time which could be fasten by special optimization of the system.